NURSING DUTIES AND ACCREDITATION STANDARDS AND THEIR IMPACTS: THE NURSING PERSPECTIVE - Adel Ghazai Almutairi, Shalan Radi Shalan Aldhafeeri, Khalid Bijad Almutairi, Madhawi Saoud Almutairi, Khulud Hammad Obaid Alshammari, Dalal Abdulrahman Fahad Almutayri (Chelonian Research Foundation, 2022)
Healthcare accreditation aims to improve quality and safety through setting standards, but impacts on nurses’ work experiences remain underexplored. This mixed methods study examined nurses’ perspectives on how accreditation processes and evolving nursing role expectations affected workload, stress, and job satisfaction across 10 hospitals pursuing accreditation in Saudi Arabia. Surveys completed by 150 nurses assessed changes pre and post-accreditation preparations. Additionally, 25 nurses participated in focus groups eliciting experiences. Surveys revealed significantly increased workload and documentation demands with accreditation, although satisfaction with quality improvements offset frustrations. Qualitative themes emphasized burnout from mounting administrative duties and tensions meeting both care and audit demands. However, nurses also noted benefits of formalization and heightened quality awareness. Ensuring adequate staffing, worklife balance policies, updated technology infrastructure, and nurses’ involvement in designing streamlined documentation are advised to support care standards attainment. This study provides insights into accreditation impacts on nursing experience from the “sharp end” of care, highlighting policy and practice strategies to optimize outcomes.